Internalization of Multicultural Islamic Religious Education at the Bustanul Mutaallimin Dawuhan Islamic Boarding School, Blitar City - Arif Muzayin Shofwan, Arif Muzayin (SINDA: Comprehensive Journal of Islamic Social Studies, 2023)
This natural phenomenological research and attention to meaning focuses on social phenomena that exist in the Bustanul Mutaallimin Islamic Boarding School in Blitar. Data collection techniques are carried out using several things, namely observation, in-depth interviews, and documentation. The data analysis technique used is descriptive-exploratory involving four components of analysis, namely domain, taxonomic, componential, and cultural theme analysis. The results of this study found the following things. First, several factors for the successful internalization of multicultural Islamic religious education in the Islamic boarding school, including: the conduciveness of the vision of the Islamic boarding school, the conduciveness of curriculum design, the conduciveness of instilling multicultural values, the conduciveness of creating a multicultural environment, and the conduciveness of designing learning places. Second, the internalization of multicultural Islamic religious education is carried out through two learning models, namely: the direct learning model and the indirect learning model. Third, the practice of internalizing multicultural Islamic religious education in Islamic boarding school is carried out in the following ways, including: organizing Islamic ta'aruf parades rahmatan lil 'ālamīn, organizing the cross-cultural dialogue, organizing collaborative activities with religions, religious organizations, and other sects, organizing practical real work on cross-cultural recitations at the Bumi FM Radio Studio owned by the Islamic boarding school, organizing multicultural documentaries, and others.